Developing a Guided Imagery Telephone-Based Tobacco Cessation Program for a Randomized Controlled Trial - Julie S Armin; Uma Nair; Peter Giacobbi; Gayle Povis; Yessenya Barraza; Judith S Gordon (SAGE Publishing, 2020)
Background/Aims: Guided imagery is an evidence-based, multi-sensory, cognitive process that can be used to increase motivation and achieve a desired behavior. Quitlines are effective, standard care approaches for tobacco cessation; however, utilization of quitlines is low. Using guided imagery-based interventions for smoking cessation may appeal to smokers who do not utilize traditional quitline services. This paper reports the development of program materials for a randomized controlled feasibility trial of a guided imagery-based smoking cessation intervention. The objective of the formative work was to ensure that program materials are inclusive of groups that are less likely to use quitlines, including men and racial/ethnic minority tobacco users. Methods: A three-phase process was used to complete formative assessment: (1) integration of evidence-based cessation practices into program development; (2) iterative small group interviews (N = 46) to modify the program; and (3) pilot-testing the coaching protocol and study process among a small sample of smokers (N = 5). Results: The Community Advisory Board and project consultants offered input on program content and study recruitment based on their knowledge of minority communities with whom they conduct outreach. Small group interview participants included members of underserved quitline populations (52.37% non-white; 55.56% men). Only 28.26% of participants had prior experience with guided imagery, but others described the use of similar mindfulness and meditation practices. Participant feedback was incorporated into program materials and protocols. Discussion: Iteratively collected feedback and pilot testing influenced program content and delivery and informed study processes for a randomized controlled feasibility trial of a telephone-delivered, guided imagery-based intervention.